ALGORITHMS AND JUSTICE: AN ERA OF UNCERTAINTY AND DOUBT - Basu, Nibedita; Dave, Rhishikesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper describes the emerging concept of algorithmic complacency and the questions it raises regarding human epistemic agency in AI-governed decision scenarios. Examining case studies of algorithmic choice architectures through the lenses of the philosophical frameworks of epistemic and hermeneutical injustice allows an analysis of how algorithmic decision environments systematically interfere with our ability to form, assess, and revise belief states. In so doing, it argues that adaptive-choice architectures and hyper-nudging techniques create a panoply of situations in which epistemic autonomy is undermined, and algorithmic opacity introduces new hermeneutical gaps that interfere with our capacity for meaning-making and world navigation. Through this analysis, which is made operational by case studies based primarily on recommendation systems, decision support tools, and content curation platforms, a rough map emerges through which the potential for AI-based architectures of choice to fundamentally change human epistemic practice is charted and possible response points are elucidated, where intervention may be made to support the preservation of epistemic agency.